Safety, pharmacokinetics, and pharmacodynamics of lumacaftor and ivacaftor combination therapy in children aged 2–5 years with cystic fibrosis homozygous for F508del-CFTR: an open-label phase 3 study. Issue 4 (April 2019) - McNamara, John J; McColley, Susanna A; Marigowda, Gautham; Liu, Fang; Tian, Simon; Owen, Caroline A; Stiles, David; Li, Chonghua; Waltz, David; Wang, Linda T; Sawicki, Gregory S
Summary: Background: The efficacy, safety, and tolerability of lumacaftor and ivacaftor are established in patients aged 6 years and older with cystic fibrosis, homozygous for the F508del-CFTR mutation. We assessed the safety, pharmacokinetics, pharmacodynamics, and efficacy of lumacaftor and ivacaftor in children aged 2–5 years. Methods: In this multicentre, phase 3, open-label, two-part study, we enrolled children aged 2–5 years, weighing at least 8 kg at enrolment, with a confirmed diagnosis of cystic fibrosis who were homozygous for the F508del-CFTR mutation. Children received lumacaftor 100 mg and ivacaftor 125 mg (bodyweight <14 kg) or lumacaftor 150 mg and ivacaftor 188 mg (bodyweight ≥14 kg) orally every 12 h for 15 days in part A (to assess pharmacokinetics and safety) and for 24 weeks in part B (to assess safety, pharmacokinetics, pharmacodynamics, and efficacy). Children could participate in part A, part B, or both. Children were enrolled into part A at five sites in the USA and into part B at 20 sites in North America (USA, 17 sites; Canada, three sites). The primary endpoints of the study were the pharmacokinetics (part A) and safety (part B) of lumacaftor and ivacaftor; all analyses were done in children who received at least one dose of lumacaftor and ivacaftor. Secondary endpoints in part A were safety and pharmacokinetics of the metabolites of lumacaftor and ivacaftor, and in part B included pharmacokinetics in children who received at least one dose of lumacaftor and ivacaftor and absolute changes from baseline in sweat chloride concentration, growth parameters, and markers of pancreatic function. This study is registered with ClinicalTrials.gov, number NCT02797132 . Findings: The study was done from May 13, 2016, to Sept 8, 2017. 12 children enrolled in part A, 11 of whom completed the 15-day treatment period and enrolled in part B. 60 children enrolled in part B, 56 of whom completed the 24-week treatment period. Safety and pharmacokinetics were consistent with the well characterised safety profile of lumacaftor and ivacaftor. In part B, most children (59 [98%] of 60 children) had one or more treatment-emergent adverse events; most events were mild to moderate in severity. The most common adverse events were cough (38 [63%] of 60), vomiting (17 [28%]), pyrexia (17 [28%]), and rhinorrhoea (15 [25%]). Serious adverse events occurred in four children: infective pulmonary exacerbation of cystic fibrosis (n=2), gastroenteritis viral (n=1), and constipation (n=1). Three (5%) of 60 children discontinued treatment because of elevated serum aminotransferase concentrations. Mean sweat chloride concentrations decreased by 31·7 mmol/L, biomarkers of pancreatic function improved (fecal elastase-1 concentrations increased and serum immunoreactive trypsinogen concentrations decreased), and growth parameters increased at week 24. Interpretation: Lumacaftor and ivacaftor were generally safe and well tolerated in children aged 2–5 years with cystic fibrosis for 24 weeks. Efficacy findings also suggest that early intervention with lumacaftor and ivacaftor has the potential to modify the course of disease. Funding: Vertex Pharmaceuticals Incorporated.